Recurrent Pleural Effusions and Elevated PTHrP: An Unusual Case of Sarcoidosis - Atchayaa Gunasekharan; Joel Thekekara; Younghwa Kwon; Farzan Irani (Greater Baltimore Medical Center, 2020)
A 63-year-old male with a past medical history of stage 3 chronic kidney disease, type 2 diabetes mellitus, hypertension, and coronary artery disease presented with recurrent symptomatic pleural effusions, low back pain and unintentional weight loss. Labs revealed elevated serum calcium and parathyroid hormone-related peptide, but normal parathyroid hormone, vitamin D, and angiotensin-converting enzyme levels. Malignancy workup was revealing for salt-and-pepper appearance of the bone marrow on MRI of the lumbar spine consistent with multiple myeloma. CT of chest, abdomen, and pelvis was negative for neoplastic process but showed a pleural effusion and calcified granulomas in hilar lymph nodes. Bone marrow biopsy of the lumbar region was subsequently conducted and revealed granulomas confirming the diagnosis of sarcoidosis. Treatment of sarcoidosis resulted in complete resolution of his symptoms and pleural effusion. This case highlights the variable presentation of sarcoidosis and its ability to mimic malignancy. Prompt recognition and treatment is essential in avoiding unnecessary costs and harm to the patient.